2020
DOI: 10.1016/j.ijnss.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Practices of caring for nursing students: A clinical learning environment

Abstract: Objective The purpose of this study was to explore, describe and illuminate nursing students’ best encounters of caring in the clinical learning environment. Caring for nursing students was emphasized and recommendations provided to enhance caring for nursing students within their clinical learning environment. Methods Qualitative data was collected by the researcher using semi-structured individual interviews and an Appreciative Inquiry (AI) methodology. Ten second yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…Sharing the experience of a clinical tutor is an effective way to increase students' understanding of relationship skills [6], [10], [22]. Not to create barriers for student competency development, institutions need to identify and address poor or negative role models immediately, even causing confusion and demotivation for students [5], [6].…”
Section: Clinic Nurses As Role Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sharing the experience of a clinical tutor is an effective way to increase students' understanding of relationship skills [6], [10], [22]. Not to create barriers for student competency development, institutions need to identify and address poor or negative role models immediately, even causing confusion and demotivation for students [5], [6].…”
Section: Clinic Nurses As Role Modelsmentioning
confidence: 99%
“…Empathy is the emotional ability to understand the feelings of others so that they can see a problem from the other person's point of view. This concept is a form of emotional intelligence characterized by the ability to listen to a speech, accept viewpoints, feel the feelings of others based on changes in expression, tone of speech, and body language [5], [33], [34]. Empathy is the behavior of being conscious and reacting mentally and emotionally to others, feeling sympathy and concern for others, especially in others who are suffering by putting themselves in that other person's position so that others seem to be a part of him.…”
Section: It Builds Empathy For Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second factor was communication. Accordingly, having the ability of an effective communication is an essential element for nursing students to feel well-being, which subsequently increases the level of their self-confidence, motivation, and self-esteem [ 48 ]. Also, Sheu et al reported that the inability to communicate with nurses is one of the most important stressors among senior students [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In particular, nursing studies have focused on caring to enhance the student clinical learning environment. 3 Further studies have noted that student-faculty relationships were an influential factor in student satisfaction. 4,5 Specifically, one study found that a positive clinical environment was directly associated with strong relationships between students and faculty.…”
Section: Introductionmentioning
confidence: 99%